1989
DOI: 10.1111/j.1365-2125.1989.tb03428.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of midazolam following orthotopic liver transplantation.

Abstract: Seven patients with chronic liver disease received a 10 mg intravenous bolus dose of midazolam immediately following orthotopic liver transplantation. Plasma samples were analysed for midazolam and ot-hydroxymidazolam by gas chromatography with electron capture detection. Data from three patients could not be evaluated. In the remaining four patients the pharmacokinetics of midazolam were essentially normal but the plasma concentrations of ot-hydroxy-midazolam were higher than those found in healthy subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Also in the study by Howie et al, prolonged sedation with midazolam did not affect hepatocellular integrity [14]. Similarly, midazolam did not have a prolonged duration of action in liver transplantation patients [5]. In addition to liver function, some authors showed that postoperative renal function preserves in TIVA with propofol [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in the study by Howie et al, prolonged sedation with midazolam did not affect hepatocellular integrity [14]. Similarly, midazolam did not have a prolonged duration of action in liver transplantation patients [5]. In addition to liver function, some authors showed that postoperative renal function preserves in TIVA with propofol [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the aim of the present prospective randomized double blind clinical trial was to investigate the effect of total intravenous anesthesia (TIVA) with propofol on postoperative hepatic and renal functions. We chose midazolam, a short-acting benzodiazepine, as a comparator drug because it has been reported to be safe and not to cause substantial hepatic or renal injury [5][6][7]. Although propofol and midazolam are the most popular IV anesthetics, to our knowledge, no prospective study has compared their liver and renal effects after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the patient’s medical status and American Society of Anesthesiology grading must be assessed in order to treat the patient in the most appropriate setting. In particular, patients who have received a liver or kidney transplant may be more susceptible to alterations in the metabolism and excretion of midazolam (61). Medical advice should be sought regarding the use of benzodiazepines.…”
Section: Patient Managementmentioning
confidence: 99%
“…Recovery of drug metabolism capacity occurs immediately after reperfusion of the liver graft. Considerable metabolic capacity has been demonstrated by the liver grafts for morphine and midazolam (52,70). Renal dysfunction is common in liver transplant recipients, and renal excretion is an important pharmacological consideration for these patients (9,31,52).…”
Section: Specific Anesthetic Considerationsmentioning
confidence: 99%